Reflexão: uma base para mudança na prática pedagógica - PINHEIRO, Eliana Gomes (2024)
This Memorial is an approach of important points of the student life, professional and academic of the course of Full Degree in Pedagogy of my, its purpose is to describe childhood memories, from the first contact with the personal and professional experiences acquired, passing through the entrance For the Full Degree in Pedagogy Course of the Federal University of Pará, which was the fulfillment of the dream to reach academic formation, a dream that for me, woman of simple origin of the riverside region often seemed impossible. I still draw a reflection on the process of knowledge construction during the period of training and learning, as well as the changes and new directions in my pedagogical practices, facing a new understanding of the theories and educational conceptions of the pedagogue, acquired in my academic formation.